Development of a novel PTT assay for mutation detection in PALB2 large exons and PALB2 screening in medullary breast cancer - Poumpouridou,N.; Goutas, N.; Tsionou,C.; Dimas, K.; Lianidou,E.; Kroupis, C. (Fam.Cancer, 2016)
Beyond BRCA1 and BRCA2 genes, PALB2 (Partner and localizer of BRCA2) emerges as the third breast cancer susceptibility gene due to its role in the same DNA repair pathway: homologous recombination. In most populations studied so far, PALB2 mutations are detected in 1-2% of BRCA negative female patients. PALB2 gene contains 13 exons; exons 4 and 5 consist 65% of the coding area. We developed a protein truncation test (PTT) for quick screening of truncating pathogenic mutations of these two large exons. Specific primers were de novo, in silico designed and the PTT-PCR products were translated in the presence of biotinylated lysine and detected colorimetrically. The assay was initially tested in 30 patients with hereditary breast cancer, negative for BRCA mutations and then, in 17 patients with the rare medullary breast cancer subtype. Small PALB2 exons were screened with high-resolution melting curve analysis (HRMA) and the large DNA rearrangements with multiplex ligation-dependent probe amplification (MLPA). Any alterations detected were verified by Sanger DNA Sequencing. The developed PTT methodology is highly specific for clinical significant mutations; positive control samples that produce truncated PALB2 peptides were correctly identified and the method was accurate when compared to DNA sequencing. We did not detect any deleterious PALB2 mutation in both groups of patients. HRMA and MLPA were also negative for all tested samples. However, our novel, fast and cost-effective PTT method for pathogenic mutation detection of the two large PALB2 exons can be applied in screening of a large number of breast cancer patients